Pengaruh Kesehatan, Tingkat Pendidikan, dan Upah Minimum terhadap Kemiskinan pada Provinsi Jawa Barat Tahun 2019-2020 - Nurlaila Maysaroh Chairunnisa; Yuha Nadhirah Qintharah (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2022)
This study aims to examine the effect of health, education level, and minimum wage on poverty. The sample in this study was the city and district of West Java Province in 2019-2020. Data analysis in this study used multiple regression. This study found that health had no effect on poverty, education had a significant negative effect on poverty, and the city/district minimum wage had no effect on poverty. Keywords: health, education level, minimum wage, poverty